THE USE OF GOOGLE DOCS TO IMPROVE STUDENTS’ WRITING ABILITY - Afdaliah, Nihla; Uswatunnisa, Uswatunnisa; Marliana, Rina (Inspiring: English Education Journal, 2019)
The objective of this research was to find out whether or not the use of Google Docs improved the students? writing skill and to find out the students? interest in learning writing by using Google Docs. This research applied a quasi-experimental design with an experimental class and a control class. The procedure of collecting data involved administering a pre- test, treatments and a post- test. The sample consisted of 54 students who were chosenby using cluster random sampling. The instruments of this research were writing text and questionnaire. The result of the data analysis showed that the mean score of experimental class was higher than that of control class and the result of hypothesis testing using independent T-Testin SPSS 16showed that t value is greater than t table, so H1  was accepted. It can be concluded that the use of Google Docs significantly improves the students? writing skill and It also found that students were interested in learning writing by using Google Docs that is proved from their questionnaire result.